Expression of cell-wall related genes is highly variable and correlates with sepal morphology - Hartasánchez, Diego A.; Kiss, Annamaria; Battu, Virginie; Soraru, Charline; Delgado-Vaquera, Abigail; Massinon, Florian; Brasó-Vives, Marina; Mollier, Corentin; Martin-Magniette, Marie-Laure; Boudaoud, Arezki; Monéger, Françoise (Peer Community Journal, 2023)

(untitled)
Control of organ morphology is a fundamental feature of living organisms. There is, however, observable variation in organ size and shape within a given genotype. Taking the sepal of Arabidopsis as a model, we investigated whether we can use variability of gene expression alongside variability of organ morphology to identify gene regulatory networks potentially involved in organ size and shape determination. We produced a dataset composed of morphological parameters and genome-wide transcriptome obtained from 27 individual sepals from wild-type plants with nearly identical genetic backgrounds, environment, and developmental stage. Sepals exhibited appreciable variability in both morphology and transcriptome, with response to stimulus genes and cell-wall related genes displaying high variability in expression. We additionally identified five modules of co-expressed genes which correlated significantly with morphology, revealing biologically relevant gene regulatory networks. Interestingly, cell-wall related genes were overrepresented in two of the top three modules. Overall, our work highlights the benefit of using coupled variation in gene expression and phenotype in wild-type plants to shed light on the mechanisms underlying organ size and shape determination. Although causality between gene expression and sepal morphology has not been established, our approach opens the way to informed analysis for mutant characterization and functional studies.